Depression among diabetic patients visiting a diabetes center in Nepal - Pahari, Durga Prasad; Upadhyay, Radhika; Sharma, Chandra Kala (Health Prospect, 2018)
Introduction: Depression is a major co-morbidity associated with diabetes. This study aims to assess the prevalence and determine factors associated with depression among diabetic patients visiting a diabetes center in Lalitpur, Nepal. Methods: This is a cross-sectional study of diabetic patients visiting a diabetes center in Kathmandu, Nepal. 203 diabetic patients were recruited in a period of two months. A validated and reliable Beck Depression Inventory Scale was used to identify and classify depression. Diabetes status was self-reported. Prevalence of depression, socio-demographic and diabetes related characteristics were calculated using frequency and percentages. Association was analyzed using chi-squared test. Statistical significance was determined at p<0.05. Bivariate logistic regression was performed to identify unadjusted odds ratio with 95% CI. Then, multivariate logistic regression model was designed for those variables significant at bivariate level to calculate adjusted odds ratio with 95% CI. Results: The prevalence of depression among diabetic patients was 34% (Mild - 17.7%, Moderate - 13.8% and Severe - 2.5%). Diabetic patients with secondary or above educational level were less than half likely to be affected by depression compared to patients with no formal school education [AOR:0.42]. Similarly, diabetic patients on insulin therapy were twice likely to be affected by depression compared to patients on oral hypoglycemic agents [AOR: 2.08] and patients having other comorbidity along with diabetes were also twice likely to be affected by depression [AOR:2.18]. Patients with stressful life events in the past were twelve times more likely to have depression compared to patients with no such events in the past [AOR: 12.33]. Conclusion: More than one third of the diabetic patients have some degree of depression. Factors such as no schooling, being on insulin therapy, having other comorbid conditions along with diabetes and stressful life events in the past among diabetic patients kept them at higher risk of depression. These factors should be focused in program for prevention and control of depression among diabetic patients in Nepal.